Ground support design under highly stressed conditions - Vakili, A; Sandy, MP; Mathews, M; Rodda, B (Ground Support 2013: Seventh International Symposium on Ground Support in Mining and Underground Construction, 2013)
Development advance rates in mining projects have been increasing substantially in recent years and the number of mines operating at greater depth in Australia and other countries is increasing. In general, this requires more systematic ground support design in more severe ground conditions such as those that exist in highly stressed and highly anisotropic rock masses. In particular, more attention is required in relation to the timing of ground support installation and the interaction between the ground support and the rock mass. This paper describes a numerical modelling method that can be used as a tool to optimise the ground support design in more severe ground conditions. A new quantitative guideline is presented, summarising the typical response of ‘massive’, ‘moderately jointed’ and ‘highly jointed’ rock masses to increasing stress levels. A case study is also presented, in which advanced modelling techniques were used to improve the ground support performance through optimisation of timing and stiffness of the ground support system at the CSA mine in Cobar, New South Wales. The ground displacement and closure strain were carefully monitored at CSA, and a comprehensive development and stope damage database was compiled. The numerical model was then accurately calibrated using the instrumentation data and the damage history of the mine.